Estimation of reliability series stress – Strength model based on power Rayleigh distribution - Ahmed, Abdulrhaman A. J.; Batah, Feras Sh. M. (AIP conference proceedings, 2023)
The estimate of the parameter and reliability Series Rs = p[v<min (t1, t2, t3, … …. tr,] system in stress – strength model with (Strength (v)) subject to a( stress( t)) that our motivaction in this paper. They follows the power Rayleigh distribution PR(ʓ,β). We used two data sets with criteria( −2 ln(l), AIC, BIC, AICC, KS, HQIC, p−value). The paper investgates and proposes some estimation methods. Comparsions between these methods utilized three criteria such as (bisd), (MSE) and (MAPE). Monte Carlo simulation study and real-data set uses to concluded the results of this paper.